2007
DOI: 10.1111/j.1745-459x.2007.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

The Just‐about‐right Intensity Scale: Functional Analyses and Relation to Hedonics

Abstract: This study assessed the meaning of just-about-right (JAR) categories when used with a 5-point intensity scale. The panelists comprised both consumer and in-house respondents. The JAR categories have various meanings as perceived by the respondents: "prefer product," "very good," "I like the product," "like it very much," "highly favorable," "high acceptability," "desirable like the product," "best for the situation" and "correct." Thus, the JAR meanings invoke preference and acceptability. This article present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 7 publications
1
42
0
4
Order By: Relevance
“…Since JAR scales utilize two different directions, interpretation of the meaning of JAR and analysis of the scale compounding respondents' heterogeneity preferences always require attention. Gacula et al (2007) found that consumers generally revealed the meaning of 'just-about-right' as their preference and acceptability about the attributes. In the same study, Gacula, Rutenbeck, Pollack, Resurreccion, & Moskowitz (2007) introduced two analysis methods of JAR scales: 1) dividing analysis below and above-JAR deviation and 2) signal-to-noise ratio (SNR) statistics.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since JAR scales utilize two different directions, interpretation of the meaning of JAR and analysis of the scale compounding respondents' heterogeneity preferences always require attention. Gacula et al (2007) found that consumers generally revealed the meaning of 'just-about-right' as their preference and acceptability about the attributes. In the same study, Gacula, Rutenbeck, Pollack, Resurreccion, & Moskowitz (2007) introduced two analysis methods of JAR scales: 1) dividing analysis below and above-JAR deviation and 2) signal-to-noise ratio (SNR) statistics.…”
Section: Participantsmentioning
confidence: 99%
“…Gacula et al (2007) found that consumers generally revealed the meaning of 'just-about-right' as their preference and acceptability about the attributes. In the same study, Gacula, Rutenbeck, Pollack, Resurreccion, & Moskowitz (2007) introduced two analysis methods of JAR scales: 1) dividing analysis below and above-JAR deviation and 2) signal-to-noise ratio (SNR) statistics. The first method is useful to provide heterogeneity preference and the direction of developments.…”
Section: Participantsmentioning
confidence: 99%
“…The Taguchi's signal-to-noise ratio (SNR) (Equation 1) was calculated in order to know the robustness of acceptability mean values of samples (Gacula, 1993;Gacula et al, 2007;Pastor et al, 1996),…”
Section: Discussionmentioning
confidence: 99%
“…These results show that depending on the composition of the vanilla beverage samples, the addition of inulins with a different average chain length can produce products whose sensorial differences are clearly perceived by the consumer. In order to analyse the relationship between the overall acceptability of samples and the appropriateness of each attribute levels, plots of acceptability versus JAR score deviation from category 3 (the just about right anchor of the scale) were used (Gacula et al, 2007). Two groups of data will emerge from this calculation, one for those individuals who feel that the product has too little of the attribute (below the JAR), and the other for those individuals who feel that the product has too much of the attribute (above the JAR).…”
Section: Influence Of Inulin Average Chain Length On Physicochemicalmentioning
confidence: 99%
“…O limiar terminal corresponde à concentração de um gosto acima da qual não há aumento da percepção do mesmo (MEILGAARD et al, 1999 (GACULA et al, 2007). Embora concentrações ideais de determinado atributo sejam consideradas similares ou iguais a concentrações mais aceitas ou de preferência, diversos estudos mostram não existir relação direta entre as escalas empregadas nos dois testes (EPLER et al, 1998).…”
Section: Testes De Sensibilidade Gustativaunclassified